A systematic review of relationships and sex education outcomes for students with intellectual disability reported in the international literature. Issue 7 (13th June 2022) - Paulauskaite, L.; Rivas, C.; Paris, A.; Totsika, V.
Abstract: Background: Little is known about how to evaluate relationships and sex education (RSE) delivered to students with intellectual disability and what stakeholders perceive are important outcomes. The present study aimed to systematically review existing studies on outcomes of RSE, as the first step in the development of a core outcome set (COS) for students with intellectual disability. Method: A systematic literature process included two stages: (1) searching for studies reporting on RSE outcomes for students with intellectual disability and (2) studies reporting on measurement properties (e.g. validity, reliability and responsiveness) of standardised instruments identified in stage 1. Results: A total of 135 RSE outcomes were extracted from 42 studies: 43 outcomes for students in secondary education and 92 outcomes for students in further education. No RSE outcomes were reported for primary education. Outcomes referred to the human body, hygiene, relationships, sexuality, sex and its consequences, inappropriate and appropriate social and sexual behaviour, keeping safe, emotional vocabulary and positive self‐esteem. Outcomes were predominantly knowledge‐based, rather than relating to skills and attitudes development. Students with intellectual disability, parents and teachers perceive different RSE outcomes meaningful. Five instruments were used to measure the outcomes, but none have established psychometric properties with this population. Conclusions: The comprehensive list of RSE outcomes for students with intellectual disability will be used to inform the next steps of a Core Outcome Set needed for RSE evaluations in research and education settings. There is an urgent need to develop standardised instruments validated for students with intellectual disability.